Análisis de la calidad de absorción visual de las unidades del paisaje del páramo de Cuturiví Chico de la parroquia Pujilí, propuesta de conservación, 2023. - Tulcán Guanina, Maritza Estefanía (2023)
The research project was developed to determine the quality and visual fragility of the components that make up the units of the Cuturiví Chico páramo, located in the Pujilí parish, Cotopaxi Province, so that the study of the different situations of the landscape modified by human action, that is, the landscape units, the quality of visual absorption (CAV) and then the fragility and visual sensitivity. For this, we used a methodology focused on the characterization of the landscape units., based on the BLM Calidad Visual program and its VRM (Visual resource management) method, which allowed establishing values according to numerical weighting scales focused on the delimitation of the components of relief, color, texture, slope, vegetation, scenic context, and spatial configuration. A qualitative approach helped the analysis of images of the study place, agreeing to give values to each of the criteria and mechanisms determined within the visual assessment of the landscape through the analysis od pictures registered in-situ in the area. The results established that the páramo has an average visual quality of class B, where its areas have variety in shape, color, line, and texture, but that they are common in the studied region and not exceptional with an average of 14.3 the visual absorption capacity belongs to class I, with the fragility of the very fragile landscape with an average of 24.8 with visual sensitivity of class 4 with low quality and high medium CAV and visual fragility establishes an average of 20, 8, therefore, the páramo is placed in Class II, therefore, the landscape has a moderate fragility; Therefore, we concluded that it is necessary to propose a conservation, protection, and recovery plan for the study area of the Cuturiví Chico páramo of the Pujilí parish.